A Assessment of Potential Damage and Loss of Subak Land Use Due to Flood Hazard in South Denpasar District, Denpasar City - Sianturi, Harrixon Sangputra; Sumarniasih, Made Sri; Wiguna, Putu Perdana Kusuma; Narka, I Wayan; Bhayunagiri, Ida Bagus Putu; Mega, I Made (Universitas Negeri Semarang, 2025)
South Denpasar District has an elevation of 0–12 meters above sea level and is categorized as a lowland area, making it prone to flood disasters. Flooding can cause damage and economic losses, particularly in the agricultural sector on subak lands. This study aims to calculate the potential damage and losses in subak land use in South Denpasar. The methods used include the Topographic Wetness Index (TWI) to analyze flood and damage potential, as well as field surveys for validation and loss estimation. The data used include DEM SRTM data, the Indonesian Topographic Map (RBI), the subak boundary map of South Denpasar District, and satellite imagery from Google Satellite. Data from the Department of Agriculture include subak area data. Data from the Agricultural Extension Center (BPP) and subak heads (pekaseh) include data on the cost components of subak production per hectare. Data from the Department of Public Works, Water Resources Division, include subak irrigation data and the cost components for constructing concrete irrigation channels per meter. The results show that subak land in South Denpasar has high damage potential covering 91,732 ha (20,48%), medium damage potential at 133,548 ha (29,81%), and low or no damage at 222,701 ha (49,71%). Areas with the largest subak damage potential are Subak Kerdung and Subak Kepaon. The potential damage to subak irrigation networks is classified as high 974,07 m (8,00%), medium 4.107,12 m (33,71%), and low or none 7.101,99 m (58,29%). The longest irrigation damage potentials are found in Subak Kerdung and Subak Intaran Barat. The total estimated subak loss in South Denpasar District is calculated by summing the losses from high and medium damage potential for each variable. The estimated loss for subak production is IDR 1,564,288,000, while the irrigation loss is IDR 1,496,626,727, resulting in a total potential loss of IDR 3,060,914,727. The highest losses are found in Subak Kerdung and Subak Kepaon. Policy recommendations include strengthening irrigation infrastructure, disaster mitigation training, and preserving the subak system through land conservation.